Stalling fertility decline of Israeli Muslims and the demographic transition theory. (2nd September 2019) - Staetsky, L. Daniel
Abstract : The total fertility of Muslims in Israel declined from a level of nearly ten children per woman in the mid-1960s to about 4.5 children per woman in the mid-1980s. It then remained close to 4.5 children per woman for nearly 20 years. The reasons for this long stall in the fertility decline are not understood. This paper explores the roles of marriage patterns and marital fertility in the development of the stall in Muslim fertility decline in Israel from 1986 to 2003. The results show that the fertility decline among Muslims in Israel stalled owing to abrupt discontinuations of declines in both the proportion married and marital fertility. The former is explained by the relaxation of a marriage squeeze that had resulted from past fluctuations in fertility. These findings have implications for debates on the determinants of fertility stalls and for demographic transition theory.